2020
DOI: 10.1016/j.psychres.2020.113117
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness: A signature mental health concern in the era of COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
739
8
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 787 publications
(814 citation statements)
references
References 6 publications
50
739
8
17
Order By: Relevance
“…Awe could be construed as a critically beneficial emotion to strengthen connections with the rest of humanity and the physical world. In rapidly changing circumstances such as the COVID-19 pandemic, social connections are key to mitigating the social and psychological consequences of new public policy measures (e.g., Brooks et al, 2020;Fiorillo & Gorwood, 2020;Killgore et al, 2020;Usher et al, 2020). The lockdowns may produce novel experiences of awe and opportunities to transcend the self in the consideration of the common good; such a capacity may be critical to the challenges imposed by the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Awe could be construed as a critically beneficial emotion to strengthen connections with the rest of humanity and the physical world. In rapidly changing circumstances such as the COVID-19 pandemic, social connections are key to mitigating the social and psychological consequences of new public policy measures (e.g., Brooks et al, 2020;Fiorillo & Gorwood, 2020;Killgore et al, 2020;Usher et al, 2020). The lockdowns may produce novel experiences of awe and opportunities to transcend the self in the consideration of the common good; such a capacity may be critical to the challenges imposed by the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence in the context of COVID-19 reports high levels of distress and loneliness in US regions with quarantine or shelter-in-place guidelines [35][36][37][38]. In the UK, 36% of respondents reported feeling sometimes or often lonely during COVID-19 [39], and Bu et al, [40] found that prevalence of severe loneliness was 14% and remained relatively stable over 6 weeks of lockdown.…”
Section: Risk Factors For Lonelinessmentioning
confidence: 99%
“…Studies have found that more frequent in-person contact mitigates the impact of the pandemic on loneliness [37,38], and that living with others, larger social network size, and greater social support are protective factors [40]. Furthermore loneliness in the current pandemic context is associated with increased depression, anxiety and suicidal ideation in the US [36,43], and with greater depression, anxiety, and stress in the UK [44]. In Poland, loneliness had a negative impact on mental health symptoms and increased participants' affective response to aspects of the COVID-19 crisis [42].…”
Section: Risk Factors For Lonelinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Loneliness and social isolation are becoming increasingly recognized as serious public health concerns, with effects on both mental and physical health [ 1 , 2 ]. Especially during the (present) world-wide COVID-19 pandemic with the resulting lockdowns and social distancing regulations, loneliness and social isolation pose particularly urgent problems for a large part of the population [ 3 , 4 , 5 ]. Research suggests that feelings of connectedness are a better predictor of a number of health outcomes than the mere number of social contacts [ 6 ], suggesting that feelings of connectedness can play a key role in maintaining good (mental) health when social distancing is required.…”
Section: Introductionmentioning
confidence: 99%